Network Meta-Analysis of Calcitonin Gene-Related Peptide Receptor Antagonists for the Acute Treatment of Migraine - Xu, Fang; Sun, Wenjun (Frontiers in Pharmacology, 2019)
Background: Research has indicated that calcitonin gene-related peptide (CGRP) antagonists can be effective in the acute treatment of migraine. Six major drugs are included within this category: telcagepant, olcegepant, BI 44370, rimegepant (BMS-927711), MK3207, and ubrogepant. However, no previous studies have performed network meta-analyses to directly compare the effects of these drugs. In the present study, we assessed the therapeutic qualities of these six different drugs to inform further clinical research. Methods: We searched PubMed, Embase, Ovid MEDLINE, Web of Science, and the Cochrane Central Register for Controlled Trials for relevant randomised controlled trials (RCTs) published through to October2018. Two reviewers performed a network meta-analysis of efficacy and toxicity on the basis of odds ratios (ORs). Results: Ten RCTs involving 8174 patients were included in our analysis. Olcegepant (OR:4.09;CI:1.81,9.25), ubrogepant (OR:2.11;CI:1.10,4.05), and BI 44370 (OR:3.36;CI:2.24,5.04) were more effective in ensuring pain relief 2 h after treatment than was placebo treatment. BI 44370 was associated with an increased risk of adverse events (AEs) when compared with placebo treatment (OR:1.57;CI:1.32,1.88).Surface under the cumulative ranking (SUCRA) analysis revealed that olcegepant was most effective and ubrogepant was associated with the lowest risk of adverse events among the six treatment options. Conclusion: Olcegepant was more effective and ubrogepant was lower toxicity than the remaining treatments. CGRP antagonists are promising for the acute treatment of migraine, especially among patients who are unable to take triptans.